In vitro and in vivo characterization of citral and limonene combinations against Vibrio campbellii in brine shrimp - Xiaoting Zheng; Annelies M. Declercq; Daisy Vanrompay; Adam F. Feyaerts; Patrick Van Dijck; Peter Bossier (Aquaculture, 2024)

Keratinocyte-specific ablation of Mcpip1 impairs skin integrity and promotes local and systemic inflammation - Piotr Konieczny; Agata Lichawska-Cieslar; Patrycja Kwiecinska; Joanna Cichy; Roza Pietrzycka; Weronika Szukala; Wim Declercq; Michael Devos; Agnieszka Paziewska; Izabela Rumienczyk; Maria Kulecka; Michal Mikula; et al. (Journal of Molecular Medicine, 2019)

Influence of the bordering shelves on nutrient distribution in the Arctic halocline inferred from water column nitrate isotopes - F. Fripiat; M. Declercq; C. J. Sapart; L. G. Anderson; V. Bruechert; F. Deman; D. Fonseca‐Batista; C. Humborg; A. Roukaerts; I. P. Semiletov; F. Dehairs (Limnology and Oceanography, 2018)
The East Siberian Sea and contiguous western Arctic Ocean basin are characterized by a subsurface nutrient maximum in the halocline, generally attributed to both Pacific inflow and intensive remineralization in shelf bottom waters that are advected into the central basin. We report nitrogen and oxygen isotopic measurement of nitrate from the East Siberian Sea and western Eurasian Basin, in order to gain insight into how nitrate is processed by the microbial community and redistributed in the Arctic Ocean. A large decoupling between nitrate δ 15 N and δ 18 O is reported, increasing and decreasing upward from the Atlantic temperature maximum layer toward the surface, respectively. A correlation between water and nitrate δ 18 O indicates that most of the nitrate (> 60%) at the halocline has been regenerated within the Arctic Ocean. The increase in nitrate δ 15 N correlates with the fixed N deficit, indicating a causal link between the loss of fixed N and the 15 N enrichment. This suggests that a significant share of benthic denitrification is driven by nitrate supplied by remineralization and partial nitrification, allowing residual 15 N‐enriched ammonium to diffuse out of the sediments. By increasing nutrient concentrations and fixed N deficit in shelf bottom waters, this imprint is attenuated offshore following advection into the halocline by nitrate regeneration and mixing. Estimation of the sedimentary isotope effect related to benthic denitrification yields values in the range of 2.4–3.8‰, with its magnitude driven by both the degree of coupling between remineralization and nitrification, and fixed N concentrations in shelf bottom waters.

First isolation of Vibrio tapetis and an atypical strain of Aeromonas salmonicida from skin ulcerations in common dab ( Limanda limanda ) in the North Sea - M Vercauteren; E De Swaef; A Declercq; L Bosseler; S Gulla; S Balboa; J L Romalde; L Devriese; H Polet; F Boyen; K Chiers; A Decostere (Journal of Fish Diseases, 2018)
Skin ulcerations rank amongst the most prevalent lesions affecting wild common dab ( Limanda limanda ) with an increase in prevalence of up to 3.5% in the Belgian part of the North Sea. A complex aetiology of these ulcerations is suspected, and many questions remain on the exact factors contributing to these lesions. To construct the aetiological spectrum of skin ulcerations in flatfish, a one‐day monitoring campaign was undertaken in the North Sea. Fifteen fish presented with one or more ulcerations on the pigmented and/or non‐pigmented side. Pathological features revealed various stages of ulcerations with loss of epidermal and dermal tissue, inflammatory infiltrates and degeneration of the myofibers bordering the ulceration, albeit in varying degrees. Upon bacteriological examination, pure cultures of Vibrio tapetis were retrieved in high numbers from five fish and of Aeromonas salmonicida in one fish. The V. tapetis isolates showed cross‐reactivity with the sera against the representative strain of serotype O2 originating form a carpet‐shell clam ( Ruditapes descussatus ). Moreover, the A. salmonicida isolates displayed a previously undescribed vapA gene sequence (A‐layer type) with possible specificity towards common dab. Further research is necessary to pinpoint the exact role of these agents in the development of skin ulcerations in common dab.

β-Alanine does not act through branched-chain amino acid catabolism in carp, a species with low muscular carnosine storage - F. Geda; A. Declercq; A. Decostere; A. Lauwaerts; B. Wuyts; W. Derave; G. P. J. Janssens (Fish Physiology and Biochemistry, 2015)

White necrotic tail tips in estuary seahorses, Hippocampus kuda , B leeker - A M Declercq; K Chiers; W Van den Broeck; A Rekecki; S Teerlinck; D Adriaens; F Haesebrouck; A Decostere (Journal of Fish Diseases, 2014)

Antimicrobial susceptibility pattern of F lavobacterium columnare isolates collected worldwide from 17 fish species - A M Declercq; F Boyen; W Van den Broeck; P Bossier; A Karsi; F Haesebrouck; A Decostere (Journal of Fish Diseases, 2013)
Flavobacterium columnare is the causative agent of columnaris disease in diverse fish species worldwide. Although columnaris is an important disease, the antimicrobial susceptibility pattern of F . columnare is not well studied. Thus, the purpose of this study was to test the in vitro antimicrobial susceptibility of 97 F . columnare isolates collected worldwide between 1987 and 2011 from 17 fish species. The broth microdilution technique was utilized for reliable testing of these fastidious organisms. None of the isolates displayed acquired resistance to florfenicol, gentamicin, ormetoprim‐sulfadimethoxine and trimethoprim‐sulfamethoxazole. Acquired resistance to chloramphenicol was detected in 1%, to nitrofuran in 5%, to oxytetracycline in 11% and to enrofloxacin, flumequine and oxolinic acid in 10%, 16% and 16% of the isolates, respectively, as reflected by a bimodal or trimodal distribution of their minimum inhibitory concentrations ( MIC s). One isolate showed acquired resistance towards several antimicrobial agents including erythromycin. Another isolate revealed acquired resistance towards – amongst others – ampicillin. The isolates displaying acquired resistance originated from ornamental fish species or V ietnamese catfish, except for two isolates coming from wild channel catfish in which acquired resistance was encountered towards oxytetracycline only. Fifty per cent of the resistant isolates from ornamental fish were shown to have acquired resistance against three classes of antimicrobial agents, assigning these isolates as multiple resistant. These data might indicate less prudent use of antimicrobials especially in ornamental fish species.

Modelling river-floodplain interaction during flood propagation - D. Meire; L. De Doncker; F. Declercq; K. Buis; P. Troch; R. Verhoeven (Natural Hazards, 2010)

Effect of 17β-estradiol on the in vitro differentiation of murine embryonic stem cells into the osteogenic lineage - S. Tielens; F. Wymeersch; H. Declercq; M. Cornelissen (In Vitro Cellular & Developmental Biology - Animal, 2008)